Elusive Parnassius mnemosyne (Linnaeus, 1758) larvae: habitat selection, sex determination and sex ratio (Lepidoptera: Papilionidae) - P. Vlasánek; A. Bartonová; F. Marec; M. Konvicka (SHILAP, 2017)
The charismatic and regionally declining Parnassius mnemosyne (Linnaeus, 1758) is notable for surpluses of males in mark-recapture studies, as well as for poor detectability of its larvae, which develop on spring ephemeral plants, Corydalis spp. In order to study whether the bias towards male exists already in larval stage, we searched for the larvae at three localities in the Czech Republic and attempted to sex the larvae using two alternative methods: (i) by identification of the female specific sex chromatin formed by multiple copies of the W chromosome in polyploid somatic nuclei of the Malpighian tubule cells and (ii) by dissection of ovaries and testes. Finding the larvae in the field was extremely difficult, and 38 person-days of fieldwork yielded only 78 larvae. Consistent with the literature, they dwelled under sparse canopy of oak dominated mature woodlands or on woodland margins. Sexing by genitalia dissection worked well (N = 22) and revealed a prevalence of females (16 vs. 6). In contrast, the identification of sex chromatin was not possible as sex chromatin was absent (N = 56). Further cytogenetic analysis confirmed the haploid number of chromosomes n = 29, which is by one smaller than in the congeneric Parnassius apollo (Linnaeus, 1758). This reduction of chromosome number is probably the result of a fusion of sex chromosomes with a pair of autosomes, a situation not uncommon in Lepidoptera. The female-biased larval sex ratio, contrasting with male biases found so often in adults, is based on just 22 genitally dissected larvae, and may be biased by faster growth rate of males.